Strategi Komunikasi dalam Pemasaran Afiliasi Tiktok di PT Nutrifood Indonesia - Raden Roro Fatimah Azzahra Aulia; Hudi Santoso (Program Studi Komunikasi dan Penyiaran Islam IAI Pangeran Diponegoro Nganjuk, 2025)
This research explores the communication strategy of affiliate marketing implemented by PT Nutrifood Indonesia through TikTok using the AIDA model (Attention, Interest, Desire, Action) approach. TikTok is chosen for its potential to reach a young audience through short and engaging content. This study employs a descriptive qualitative method by observing Nutrifood’s affiliate content on TikTok, documenting key activities, and reviewing relevant literature. The results indicate that Nutrifood successfully captures attention through the use of trending topics, popular audio, and eye-catching visuals. Interest is generated by creatively delivering product information through affiliate creators. Desire is built through relatable storytelling and testimonials, while action is encouraged through purchase invitations and affiliate link usage. This strategy effectively increases product exposure organically and strengthens brand presence among TikTok users. The findings are expected to provide insights for digital marketing communication practitioners in optimizing social media platforms, especially affiliate programs based on content creation.